The Influencer of ESG and ERM on Financial and Non-Financial Performance of Energy Companies Listed on the Indonesia Stock Exchange for the 2019-2023 - Rachmii Syamsi; Dewi Hanggraeni (Green Publisher Indonesia, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) practices and Enterprise Risk Management (ERM) on both financial and non-financial performance of energy companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The main objective is to examine whether ESG and ERM significantly affect profitability (ROA and ROE), market valuation (Tobin’s Q), and investor trust, particularly in the context of a post-pandemic economic landscape. The novelty of this research lies in its integrated analysis of ESG and ERM as simultaneous predictors of firm performance, while incorporating non-financial outcomes that are often overlooked, such as investor perception. This study also adds value by offering empirical evidence from an emerging market context and focusing on the energy sector, which plays a strategic role in sustainable development and economic resilience. Empirical findings reveal that ESG significantly influences Return on Assets (ROA), indicating that sustainability initiatives contribute to more efficient asset utilization. However, ESG does not show a significant effect on Return on Equity (ROE) or investor trust, implying that its long-term benefits may not be immediately reflected in equity returns or stakeholder perception. Conversely, ERM demonstrates a significant impact on ROA, ROE, and investor trust, highlighting the importance of structured risk management in enhancing financial outcomes and building investor confidence. These findings suggest that both ESG and ERM can play a strategic role in improving firm performance, but their influence may vary depending on the dimension of performance being assessed.